The role of combined 24‐h multichannel intraluminal impedance‐pH monitoring in the evaluation of children with gastrointestinal symptoms suggesting gastro‐esophageal reflux disease. Issue 10 (3rd May 2016) - Hojsak, I.; Ivković, L.; Trbojević, T.; Pavić, I.; Jadrešin, O.; Mišak, Z.; Kolaček, S.
Abstract: Background: The aim of this study was to determine the role of multichannel intraluminal impedance‐pH (pH‐MII) monitoring in the diagnosis of gastro‐esophageal reflux disease (GERD) in children who presented with gastrointestinal (GI) symptoms in comparison with the results of pH‐metry alone and endoscopy. Methods: All children who underwent pH‐MII monitoring due to GI symptoms, suggestive of GERD, from October 2013 to October 2015 in Children's Hospital Zagreb, were retrospectively enrolled in the study. The cohort was divided into three groups according to age – group 1: children <1 year of age; group 2: 1–9 years of age; and group 3: ≥9 years of age. Key Results: One hundred thirty‐three patients met our inclusion criteria (73 female/60 male; mean age 9.2 years [0.19–18.0]). Gastro‐esophageal reflux disease was determined in 44 of 133 patients (33.1%) by pH‐MII and only in 21 of 133 patients (15.8%) by pH‐metry alone. Endoscopy was performed in 77 (57.9%) children and esophagitis was found in 32/77 (41.6%). The finding of esophagitis significantly correlated with the number of total reflux episodes (coef. 0.42, p < 0.001), acidic (coef. 0.26, p = 0.02), weakly acidic (coef. 0.3, p = 0.008) and non‐acidic (coef. 0.26, p = 0.02) reflux episodes detected by pH‐MII; but, no correlation was found to reflux episodes detected by pH‐metry alone (coef. 0.21, p = 0.07). Conclusions & Inferences: Compared with pH‐metry alone, pH‐MII performed significantly better in the detection of GERD in all age groups. On the basis of our data, pH‐MII had a strong correlation with endoscopically confirmed esophagitis.